Performance and training program characteristics in elite yunior female roller skier from 2021 season: A case report - Jakovics, M.; Pontaga, I. (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, Volume II, May 26th, 2023, 2023)
The purpose was to evaluate the training program, body mass composition, aerobic performance laboratory and field test results, blood hormone concentration in elite junior female roller skier in successful competition season.